Análisis de la infraestructura tecnológica utilizada por la empresa trejguinter s.a. para brindar un mejor servicio a los antiguos y futuro clientes en el área rural del cantón Vinces. - Trejo Macías, María De Los Ángeles (2022)
The present investigation is carried out with the purpose of achieving an analysis of the technological infrastructure used by the company Trejguinter S.A. to provide a better service to former and future customers in the rural area of Canton Vinces. The company has state-of-the-art equipment and trained personnel to provide an excellent service, as well as having different plans and 2 forms of connectivity for customers, the first being the radio link, which is mainly intended to reach sectors of difficult access. and fiber optics, which provides a better Internet connection, thanks to the fact that the signal goes directly through a cable with the capacity to transmit digital data modulated in light waves to the place where the client contracts the service. It has 10 metallic telecommunication towers and equipped with devices that transmit the internet signal by means of electromagnetic waves and frequencies, serving various rural sectors of the Vinces, Baba, Palenque and Salitre Cantons. Thanks to its good business management, the company Trejguinter S.A. is constantly growing, providing quality service and warmth to all its users and new customers, receiving recommendations and proposals to further improve its service. Being a company with a long history and many plans for the future.